2010
DOI: 10.1021/jf102285b
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol Profiles, Fatty Acid Composition, and Antioxidant Activities of Button Mushrooms as Affected by Tissue Part and Developmental Stage

Abstract: This article investigated the mycochemical profiles and the antioxidant activities of the lipophilic extracts of the white and brown button mushrooms. We found that only free ergosterols were present in both mushrooms at 2.04-4.82 mg/g dry matter (DM). Ergosterol concentration was higher in early growth stages but decreased as the mushrooms grew, and it distributed evenly between the caps and stems during early developmental stages but accumulated more in the caps after maturation. The photochemiluminescence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 43 publications
1
67
1
Order By: Relevance
“…The findings clearly indicate lower levels of ergosterol in comparison to other studies showing that ergosterol content in A. bisporus ranged from 4.6 to 6.4 mg/g DW (460-640 mg/100 g DW) [15,51] and more than 50 mg/100 g fresh weight [45]. However, the obtained results are in accordance with other studies that have found that the total ergosterol content in brown A. bisporus was significantly higher than in white A. bisporus [45,50,51]. The concentration of ergosterol was confirmed to be different depending on the type of fungus [15,51].…”
Section: Organic Acid Profilecontrasting
confidence: 50%
See 3 more Smart Citations
“…The findings clearly indicate lower levels of ergosterol in comparison to other studies showing that ergosterol content in A. bisporus ranged from 4.6 to 6.4 mg/g DW (460-640 mg/100 g DW) [15,51] and more than 50 mg/100 g fresh weight [45]. However, the obtained results are in accordance with other studies that have found that the total ergosterol content in brown A. bisporus was significantly higher than in white A. bisporus [45,50,51]. The concentration of ergosterol was confirmed to be different depending on the type of fungus [15,51].…”
Section: Organic Acid Profilecontrasting
confidence: 50%
“…The EC 50 values ranged from 0.8 to 3.2 mg/mL depending on the species of mushrooms. The lower values of EC 50 indicate better scavenging ability. The cultivated species A. brasiliensis and A. arvensis were distinguished by the lowest value of 0.8 mg/mL, respectively.…”
Section: Organic Acid Profilementioning
confidence: 99%
See 2 more Smart Citations
“…They can provide immunomodulating, antitumour, anti-hypercholesterolemic, antibacterial, antifungal, anti-inflammatory, antiviral, anti-diabetic, and cardioprotective effects to consumers (Reis, Martins, Vasconcelos, Morales, & Ferreira, 2017). Agaricus bisporus is the species with the highest consumption worldwide, showing a great potential to be used to enrich food matrices, mainly due to its high amount of ergosterol, a mycosterol with several bioactivities such as antioxidant, anti-inflammatory, antitumoral and antimicrobial, in addition to hypocholesterolemic effects (Gao et al, 2007;Gil-Ramírez, Ruiz-Rodríguez, Marín, Reglero, & SolerRivas, 2014;Shao, Hernandez, Kramer, Rinker, & Tsao, 2010;Yasukawa et al, 1994).…”
Section: Introductionmentioning
confidence: 99%